ANALISA PERBEDAAN “RETAIL IMAGE” MALL DAN SHOPPING CENTRE DI SURABAYA PADA SEGMEN PELAJAR DAN MAHASISWA - Edwin Japarianto (Institute of Research and Community Outreach - Petra Christian University, 2012)
In today’s shopping center growth in Surabaya, it is necessary to create an attractive image to invite consumers visit. This research try to observe retail image captured by the consumers, the observed variables are: location, merchandise, price, service, and physical facilities. Purposive sampling conducted for 100 repondents in total from student and undergraduate student based on similar charateristics of those two groups. One way ANOVA developed to analyze differences among those two groups. This research concludes that from those five factors it is known that there are few differences of consumer’s valuation image for Royal Plaza and CITO especially from the physic facilities.